Exploring university students' level of commitment towards volunteerism / Mohd Nazir Rabun ... [et al.] - Rabun, Mohd Nazir; Hj Hussin, Zaliha; Ridzuan, Mohd Rozaimy; Ab Rahman, Nur Amira Syazwani (Universiti Teknologi MARA, Shah Alam, 2017)
Volunteering has always been seen as a fundamental piece of any society. Its importance stretches from providing services to the needy all the way to enhancing the community's image, culture and even morale, hence its ever-gaining traction in the hearts of university and college students who would be the pioneers of any society's future. Special attention should be given on the involvement of students in volunteerism as they happen to be a very significant population. This study aims at exploring the demographic backgrounds of respondents who participate in volunteering activities and to gauge the level of students volunteering activities by using a sample taken from one of the Public University in Malaysia. A cross sectional study among students in University of Malaya was employed in this study. The analysis of data was based on 375 collected and usable questionnaires. The findings demonstrate a wide-ranging characteristic of the majority of the volunteers among the students in University of Malaya. The study also indicates that most of the volunteers had a moderate level of commitment towards volunteerism. The result finds that majority of respondents 86.4 percent said that they disagreed with the statement "My decision to get involved in volunteering activities is a mistake on my part (negatively worded statement)" (item 10). This item had recorded the highest mean level for the students' commitment towards volunteerism M (5.96), SD (1.61). It seems so crucial for a country to have a high level of volunteerism spirit in the youths. Moreover, it is also foreseen that the substantive results of this study will furnish information to the government and relevant parties, such as non-government organisations (NGOs) in order to devise the strategies to deal with the issue of volunteerism. Finally, it provides new effective instruments at promoting and encouraging volunteerism spirits as well as initiating relevant programmes and situating activities for university students to make it a way of life.